In Vivo Imaging of Functional Inhibitory Networks on the Mauthner Cell of Larval Zebrafish - Takahashi, Masaharu (J Neurosci, 2002)
Noninvasive in vivo calcium imaging was used to observe and characterize inhibitory circuitry in intact larval zebrafish. In the teleost hindbrain, the inhibitory network onto the major pair of reticulospinal neurons known as Mauthner cells (M-cells) has been described in detail. There are three sources of inhibition onto M-cells: recurrent inhibition mediated by an ipsilateral collateral of the M-cell axon, feedforward inhibition driven by sensory afferents, and reciprocal inhibition between bilaterally opposed M-cells. To visualize these inhibitions, M-cells were retrogradely loaded with the calcium indicator calcium green dextran. Recurrent inhibition attenuated the Ca(2+) response associated with an action potential in M-cells. Whole-cell recording revealed recurrent IPSCs, the conductance of which may underlie the shunting effect on action potentials and the attenuation of the Ca(2+) signal in M-cells. Blocking synaptic transmission within the recurrent network abolished both the Ca(2+) signal attenuation and the IPSCs. Electrical stimulation of the otic vesicle to activate VIII nerve afferents resulted in feedforward suppression of antidromically evoked test Ca(2+) responses in the contralateral M-cell. Orthodromic activation of M-cells produced a reciprocal reduction of the test Ca(2+) response in the contralateral M-cell. Thus, in the present study, we visualized the three types of inhibition and demonstrated that they are functional at 4 d after fertilization. The use of noninvasive techniques to image inhibitionin vivo suggest the plausibility of studying the hypothesis previously tested in adult goldfish that use-dependent changes in inhibitions underlie sound conditioning in escape behavior.